Management of Dystocia Due to Ventrotransverse Presentation of Fetus in a Mare - Pargi, Kalpesh Kumar; Jhamb, Dinesh; Meena, Madhu; Gaur, Mitesh; Kumar, Naveen (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia in mare due to ventrotransverse presentation with lateral deviation of head of fetus was relieved successfully by version and forced traction under epidural anaesthesia.
Keywords: Version; ventrotransverse presentation; dystocia; mare